Results-Based Financing in Education for Sub-national Government and School : A Conceptual Framework and Practical Recommendations - Terway, Arushi; Burnett, Nicholas R.; Frotté, Marina Dreux (Washington, DC: World Bank, 2022)
This study used qualitative data analysis to draw both theoretical and practical lessons from diverse experiences with RBF at the meso-level of the education sector, particularly in low and middle-income countries. We drew upon the experiences of those who have designed, implemented and/or researched such RBF initiatives. The review included four different sources of data: 1) academic literature; 2) project documents; 3) a global survey; and 4) key stakeholder interviews.